ANALYSIS OF THE INFLUENCE OF SHORT VIDEO MARKETING ON TIKTOK ON THE PURCHASE DECISIONS OF MSME PRODUCTS - Vera Selviana Adoe; Rushadiyati Rushadiyati (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to analyze the influence of short video marketing strategies on the TikTok platform on the purchasing decisions of Micro, Small, and Medium Enterprises (MSMEs) through a literature review approach. TikTok, as a short video-based social media platform, has become an increasingly popular promotional tool among MSME actors due to its ability to quickly and widely reach audiences. This study examines three main aspects, namely the influence of visual elements and narration on consumer interest, the role of interactivity and engagement in building purchase intent, and the correlation between content consumption intensity and purchase decisions. The study results show that short yet creative video content, accompanied by strong storytelling and active interaction, can enhance consumers' positive perception and encourage the intention to purchase local products. However, this research has limitations due to its reliance on secondary sources and has not yet included direct empirical data. Therefore, follow-up research based on surveys or experiments is recommended to strengthen the validity of the findings and support the development of more effective digital marketing strategies for SMEs.